Marriage and Family Therapists Relationship Commitment During the COVID-19 Pandemic - Tadros, Eman; Notice, Maxine; Fitzgerald, Michael; Gomez, Eunice; Canterbury, Morgan (Journal of Psychosociological Research in Family and Culture, 2024)
Marriage and family therapists (MFTs) are tasked with managing the wellbeing of various clients. These tasks have become difficult during the global pandemic caused by COVID-19. This study aimed to understand the influence of the global pandemic on the lives of MFTs. A sample of 72 practicing MFTs in committed relationships were surveyed. A hierarchical linear regression showed that conflict at step one and stress at step two predicted greater relationship commitment. Our findings have clinical implications for MFT’s regarding commitment difficulties and conflict resolution. Tools for relationship management of conflict along with future directions in research are discussed.